Effect of B-cation doping on oxygen vacancy formation and migration in LaBO3: A density functional theory study - Kwon, H.; Park, J.; Kim, B.-K.; Han, J.W. (Korean Ceramic Society, 2015)
LaBO3 (B = Cr, Mn, Fe, Co, and Ni) perovskites, the most common perovskite-type mixed ionic-electronic conductors (MIECs), are promising candidates for intermediate-temperature solid oxide fuel cell (IT-SOFC) cathodes. The catalytic activity on MIECbased cathodes is closely related to the bulk ionic conductivity. Doping B-site cations with other metals may be one way to enhance the ionic conductivity, which would also be sensitively influenced by the chemical composition of the dopants. Here, using density functional theory (DFT) calculations, we quantitatively assess the activation energies of bulk oxide ion diffusion in LaBO3 perovskites with a wide range of combinations of B-site cations by calculating the oxygen vacancy formation and migration energies. Our results show that bulk oxide ion diffusion dominantly depends on oxygen vacancy formation energy rather than on the migration energy. As a result, we suggest that the late transition metal-based perovskites have relatively low oxygen vacancy formation energies, and thereby exhibit low activation energy barriers. Our results will provide useful insight into the design of new cathode materials with better performance.
Keywords: Activation energy; Catalyst activity; Cathodes; Chemical activation; Density functional theory; Design for testability; Electrodes; Fuel cells; Ionic conductivity; Ions; Manganese; Oxygen; Perovskite; Positive ions; Solid oxide fuel cells (SOFC); Transition metals; Density functional theory studies; Intermediate temperature solid oxide fuel cell; Late transition metals; Mixed ionic electronic conductor (MIEC); Oxide ions; Oxygen vacancy formation energies; Oxygen vacancy migration; Vacancy formation; Oxygen vacancies